Interpretation Strategies of Contemporary Musical and Theatrical Art: Trends, Factors - Solomonova, Olga (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
Relevance of the study. The modern interpretive content main tendencies of the European and Ukrainian musical and theatrical art were analyzed. Forms of interpretation being were considered in the coordinates of the “composer-listener-performer” triad in the aspect of its correspondence to its time artistic intentions. The scientific novelty of the study is in the analysis of innovative projects most of which are not adapted to musicology and in the formulation of trends and factors of modern musical art’s interpretive policy. Main objective of the study is to determine the specifics and factors of the modern interpretations of a musical and theatrical art. Methodology. The following methods have been adapted: the interpretive — in relation to the analyzed opera projects; the hermeneutic-semantic — for the purpose of identify the interpreted works’ intonation-image specificity; the comparative — to juxtaposition the “interpretive behavior” of one work in different performance versions; the intonation-dramaturgical analysis — to study the specifics and factors of works’ interpretive versions. Results and conclusions. The modern interpretive reality initiates the emergence of radically new and the consolidation of existing non-standard trends in the work’s representation. These are: the instrumental performing theatricalization, significant expansion of the improvisation’s zone, abandonment of the opera genre canons with an emphasis on synthetic genres of performative nature and the use of bold audio, scenographic, color and light effects. The modern interpretative main trends are the actualization, the alienation and the emergence of working remote versions, the encroachment on the textual and intonational essence of a known work by adding the new material (the integral opus or the fragmentary inlay), the emergence of modern composer’s alternative role which is a co-author of a new hybrid product thanks to the connection to the work of the past. Findings of the research. The specifics and factors of work’s variant-interpretive realization are analytically argued. The main factors are the genre-intonation specificity, the synthetic and intertextual nature, the complexity and synergy of text semantic intentions, the recipient’s culturalhistorical awareness, the socio-cultural intentions’ balance of the author and his artistic will performers, the degree of text openness, the context. Prospects for further exploration in this direction. The following research areas are needed: 1) the development of new methods and terminological apparatus suitable for the modern artifacts’ analysis; 2) the analytical base’s expansion due to: a) the further accumulation of examples, b) the scientific adaptation of various genres’ works.